Mutational analysis of a Drosophila neuroblast enhancer governing nubbin expression during CNS development. Issue 8 (18th August 2018) - Ross, Jermaine; Kuzin, Alexander; Brody, Thomas; Odenwald, Ward F.
Summary: While developmental studies of Drosophila neural stem cell lineages have identified transcription factors (TFs) important to cell identity decisions, currently only an incomplete understanding exists of the cis ‐regulatory elements that control the dynamic expression of these TFs. Our previous studies have identified multiple enhancers that regulate the POU‐domain TF paralogs nubbin and pdm‐2 genes. Evolutionary comparative analysis of these enhancers reveals that they each contain multiple conserved sequence blocks (CSBs) that span TF DNA‐binding sites for known regulators of neuroblast (NB) gene expression in addition to novel sequences. This study functionally analyzes the conserved DNA sequence elements within a NB enhancer located within the nubbin gene and highlights a high level of complexity underlying enhancer structure. Mutational analysis has revealed CSBs that are important for enhancer activation and silencing in the developing CNS. We have also observed that adjusting the number and relative positions of the TF binding sites within these CSBs alters enhancer function.